The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3221/igf-esis.66.06
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of damage control of thin plate with piezoelectric actuators using finite element and machine learning approach

Asraar Anjum,
Abdul Aabid Shaikh,
Meftah Hriari

Abstract: In recent studies, piezoelectric actuators have been recognized as a practical and effective material for repairing cracks in thin-walled structures, such as plates that are adhesively bonded with piezoelectric patches due to their electromechanical effects. In this study, we used the finite element method through the ANSYS commercial code to determine the stress intensity factor (SIF) at the crack tip of a cracked plate bonded with a piezoelectric actuator under a plane stress model. By running various simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…The replacement of damaged structural components significantly impacts the life cycle cost of an airplane. In recent years, bonded composite patches have gained widespread use for repairing cracks and defects in aircraft structures [5][6][7]. This technology provides several advantages over traditional methods such as mechanical fastening or riveting, including improved fatigue behavior, restored stiffness and strength, reduced corrosion, and the ability to be readily formed into complex shapes.…”
Section: Introductionmentioning
confidence: 99%
“…The replacement of damaged structural components significantly impacts the life cycle cost of an airplane. In recent years, bonded composite patches have gained widespread use for repairing cracks and defects in aircraft structures [5][6][7]. This technology provides several advantages over traditional methods such as mechanical fastening or riveting, including improved fatigue behavior, restored stiffness and strength, reduced corrosion, and the ability to be readily formed into complex shapes.…”
Section: Introductionmentioning
confidence: 99%
“…This multi-faceted configuration emphasized the evolving complexity and sophistication of PZT-driven repair methodologies. Recently, a study has shown that the analysis of damage control in a thin cracked plate has been done by machine learning and the FE approach [17]. The authors focused on reducing human efforts and optimising the best possible solution for reducing crack damage propagation by optimizing the SIF.…”
Section: Introductionmentioning
confidence: 99%